A NEW ELECTRONIC CLINIC SYSTEM ARCHITECTURE FOR HEALTHCARE SYSTEM - NISAR, SAIMA (2013)
The Information and Communication Technology (ICT) is observed as a possibility to manage with the rising healthcare needs. ICT has improved remarkable changes in the provision and management of healthcare services. Healthcare Information Technology (IT) has received a lot of attention during past two decades. ICT can help to improve healthcare systems worldwide. These technologies can allow information to be available anywhere anytime to anyone authorized. Noticeably, with present ICT also the communication between health professionals and patients can now be done faster than ever, even real-time application. ICT has been acknowledged to be used and applied in various industries so as to get better an electronic business processes and boost consumer satisfaction. ICT has been a motivating power in the transformation ofthe rural and urban community services together with the healthcare sector